A multiphase model of tumour segregation in situ by a heterogeneous extracellular matrix. (October 2015) - Arduino, A.; Preziosi, L.
Abstract: Normal and tumour cells live in a fibrous environment that is often very heterogeneous, even characterized by the presence of basal membranes and regions with high density of collagen fibres that physiologically comparmentalize cells in well defined regions, as for in situ tumours. In case of metastatic tumours these porous structures are instead invaded by cancer cells. The aim of this paper is to propose a multiphase model that is able to describe cell segregation by thick porous structures and to relate the transition rule that determines whether cells will pass or not to microscopic characteristics of the cells, such as the stiffness of their nucleus, their adhesive and traction abilities, the relative dimension of their nucleus with respect to the dimension of the pores of the extra-cellular matrix. Abstract : Highlights: We deduce a multiphase model to describe tumour growth able to deal with cell segregation by thick ECM. We relate the transition rule of cells through the ECM to their microscopic characteristics. Simulations show the importance of nucleus stiffness and size w.r.t. ECM pore size.